2007
DOI: 10.4278/0890-1171-21.5.448
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of Environments Supporting Walking

Abstract: Multinomial models estimated the odds of people engaging in moderate walking (<149 min/wk) and in walking sufficiently to meet recommendations for health (150+ min/ wk), relative to not walking" and in walking sufficiently, relative to walking moderately. A base model consisted of survey variables, and final models incorporated both survey and environmental variables. RESULTS. Survey variables strongly associated with walking sufficiently to enhance health included household income, not having difficulty walki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 55 publications
10
100
0
1
Order By: Relevance
“…Documented elsewhere (Moudon et al, 2007) the study isolated 14 objectively measured land use and transportation infrastructure variables significantly associated with walking at health-enhancing levels. They included shorter distances to grocery stores/markets, restaurants, and retail stores, but longer distances to offices or mixed-use buildings.…”
Section: Objectively Measured Environment Variablesmentioning
confidence: 99%
“…Documented elsewhere (Moudon et al, 2007) the study isolated 14 objectively measured land use and transportation infrastructure variables significantly associated with walking at health-enhancing levels. They included shorter distances to grocery stores/markets, restaurants, and retail stores, but longer distances to offices or mixed-use buildings.…”
Section: Objectively Measured Environment Variablesmentioning
confidence: 99%
“…80 In contrast to the findings in the above studies, a study of 412 patients with acute coronary syndrome found that the 1-year risk of readmission or cardiac death was not statistically different between dog owners and nonowners (OR, 1.59; 95% CI, 0.759-3.321; P=0. 22) and was greater in cat owners than in nonowners (OR, 3.22; 95% CI, 1.44-7.19; P=0.004).…”
Section: Pet Ownership and Survival In Patients With Established Cvdmentioning
confidence: 99%
“…Recently, studies found a significant association between access to destinations and walking for transport (Cerin et al, 2007a;McCormack et al, 2008). In addition, perceptions of certain neighborhood features (e.g., well-lit streets, biking or walking trails, pedestrian safety, traffic volume and speed, disorder, and crime) are associated with physical activity (Evenson et al, 2006Franzini et al, 2008;Mota et al, 2005;Moudon et al, 2007;Sallis and Kerr, 2006;Sampson and Raudenbush, 2004).…”
Section: Introductionmentioning
confidence: 97%